Pregled glasbenega udejstvovanja tržaških Slovencev - Antoni, Luisa (Annales. Series historia et sociologia, 1998)
The article deals with the main guidelines regarding the Slovenes' music life in Trieste from 1848 to 1927. The aim of this contribution is to present a kind of a multilayered framework, within which a place was found not only by the "great" artistic spirits but by the "small" reading manifestations as well. The work began with the collection of the accessible material (articles in various magazines and dailies) and with a study of archives. The authoress's ascertainment is that the Slovenes' music life in Trieste was indeed diverse, although there are still more gaps than sufficiently dealt with spheres in this respect...
Keywords: 1848/1927; glasba; music; Trst; tržaški Slovenci; zamejski Slovenci; zgodovinski pregledi